Giant Piezoelectricity of Deformed Aluminum Nitride Stabilized through Noble Gas Interstitials for Energy Efficient Resonators (Adv. Electron. Mater. 8/2021). (12th August 2021) - Fiedler, Holger; Fuchs, Florian; Leveneur, Jérôme; Nancarrow, Mitchell; Mitchell, David R. G.; Schuster, Jörg; Kennedy, John
Abstract : Ion Beam Implantation Aluminium nitride (AlN) is central to a range of RF filter and resonators at the heart of 5G technologies. Under suitable conditions, as shown by Holger Fiedler, John Kennedy and co‐workers in article number 2100358, the piezoelectric modulus of epitaxial AlN increases by ion beam implantation of noble gases. This effect originates from a finite volume of deformed AlN with giant piezoelectricity; stabilized by incorporated noble gases into wurtzite interstitial sites.